Needs Analysis for the Development of a Training Module for Hypercontent Examination Emission Inspection at the Ministry of Transportation - Kusumawati, Galuh Indri; Wirasti, R.A. Murti Kusuma; Kusumawardani, Dwi (Journal of Education Research and Evaluation, 2020)
The main factor of air pollution in Indonesia is motorized vehicles. Motorized vehicles operating on the road will produce exhaust gas emissions which result in air pollution. In overcoming exhaust gas emissions in vehicles, the Ministry of Transportation conducts training for exhaust emission inspection, and conducts training at one of the technical implementation units, namely the Indonesian Land Transportation Polytechnic (PTDI) STTD. The purpose of this study was to conduct a needs analysis to develop a hyper content learning module for training on exhaust emission examinations, using the R&D (research and Development) method using the Derek Rowntree model. The hyper content module is a module that combines hypertext, hyperlinks, and hypermedia, and the media used in the form of video, QR code, YouTube, and cloud computing. With the development of the hyper content module, it is possible to improve the understanding and learning outcomes of training participants in studying exhaust emissions from vehicles when compared to conventional learning.